Angular-momentum transfer and alignment in deep-inelastic reactions for nearly symmetric heavy-ion systems - Pacheco, A. J.; Wozniak, G. J.; McDonald, R. J.; Diamond, R. M.; Hsu, C. C.; Moretto, L. G.; Morrissey, D. J.; Sobotka, L. G.; Stephens, F. S. (North Holland Publishin Co., 1983)
Fil: Pacheco, A. J. Comisión Nacional de Energía Atómica; Argentina